The Effectiveness of Smart Application of Integrated Licensing Services for the Public (SICANTIK) on Community Services in Gianyar Regency - Ni Luh Mita Juniari; Kadek Wulandari Laksmi P; Ni Nyoman Sri Wisudawati; Ni Wayan Lasmi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Technological advances drive development and change in various sectors of life, including the government sector. In this case, the government sector began intensively developing ICT to replace traditional public service delivery systems with digital public service delivery systems or government electronic systems (e-government). The Investment and One-Stop Integrated Services Office of Gianyar Regency has implemented an e-government service system to improve service quality so people get better service satisfaction. One of the solutions carried out by the Gianyar Regency Government providing satisfaction with non-business and non-licensing services is by utilizing the SICANTIK application which has guaranteed security because it is managed directly by the Ministry of Communication Information and integrated Online Single Submission. SICANTIK application can access nine types of permits including, a midwife practice license, nurse practice license, medical laboratory technology practice license, dental nurse license, physiotherapy license, nutrition staff license, anesthesiologist license, pharmacist license, and pharmaceutical technical personnel license. In measuring the effectiveness of performance an application in this study uses the effectiveness of application consisting of interface, navigation, content, reliability, and technical. The effectiveness measures have been carried out by the Gianyar Regency Government have been quite effective because they’ve carried out by applicable Standard Operating Procedures to increase community service satisfaction.